Retos de la contaduría pública: una visión desde los avances digitales - Ramírez Andrade, Juliana Andrea; Loango Rojas, Yorlay (Universidad Antonio Nariño, 2023)
The objective of this academic project is to make visible the fact that organizations are currently migrating towards digital transformation, which is one of the most mentioned topics in recent years, bringing with it great challenges that not only traditi onal companies face. but also, nascent or new companies.